(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the physiological processes of winter wheat under high temperature (heat) conditions, their effects on growth stages, and changes in yield indicators. The importance of selecting heat-tolerant varieties and applying appropriate agrotechnical measures in hot climates is discussed.